The Effects of Water Stress and Brassinosteroid on Apple Varieties - Sudarshna Kumari; Anju Thakur (International Journal of Economic Plants)
In Himachal Pradesh-India, Apple is mainly grown under rainfed conditions. Moreover, the rainfall is not well distributed throughout the year. Most of the rainfall is received during the monsoon and winter seasons and there is very less or no rains during critical periods of growth and development. Thus, the soil moisture generally remains very low during the summer months and a water stress condition develops. This study was undertaken to identify morphological and physio-biochemical changes in one-year-old young grafted apple seedling plants of two varieties i.e. Super Chief and Red chief (Malus×domestica Borkh) under 15 and 30 days of induced water stress followed by 0.05 ppm brassinosteroid and 0.1 ppm brassinosteroid under pot culture study. The brassinosteroid regulates a broad spectrum of plant growth and physio-biochemical processes. One of the most promising roles of brassinosteroid is their ability to confer resistance to a wide array of abiotic stresses. In my study, the maximum reduction in growth and physio-biochemical traits was registered by plants subjected to 30 of water stress as compared to 15 days of water stress than control for both cultivars. However, brassinosteroid at both concentrations could help in maintaining vital growth and physio-biochemical processes under water stress conditions. Foliar spray of brassinosteroid (0.05 ppm) prior to imposition of stress can pave the way to minimize the deleterious effects of water stress on apple plants.